Positive electrode material containing ZnO / CoO-CNT heterojunction catalyst as well as preparation method and application of positive electrode material

The ZnO/CoO-CNT heterojunction catalyst was prepared by hydrothermal synthesis and Joule heat treatment, and mixed with elemental sulfur by melt diffusion method, solving the problem of long preparation cycle and high cost of the positive electrode material of lithium sulfur battery, achieving an efficient and low-cost preparation process, significantly improving the electrochemical performance of the battery.

CN119905589APending Publication Date: 2025-04-29XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021246.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing lithium-sulfur battery cathode materials have a long preparation cycle, high manufacturing cost, low production efficiency, and difficult to achieve large-scale industrial production.

Method used

The zinc-cobalt layered double hydroxide was prepared by hydrothermal synthesis method, and then the carbon nanotubes were heat treated with Joule to form a ZnO/CoO-CNT heterojunction catalyst, and mixed with elemental sulfur by melt diffusion method to prepare the positive electrode material of lithium sulfur battery.

Benefits of technology

This method simplifies the preparation process, reduces energy consumption and cost, improves production efficiency, forms a uniformly dispersed heterostructure catalyst, and significantly improves the electrochemical performance of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905589A_ABST
    Figure CN119905589A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst as well as a preparation method and application of the positive electrode material. The preparation method comprises the following steps: firstly, synthesizing zinc-cobalt layered double hydroxide (ZnCo-LDH), mixing the zinc-cobalt layered double hydroxide (ZnCo-LDH) with a carbon nanotube (CNT), uniformly grinding, and carrying out Joule heat treatment on the obtained mixture to obtain a derivative ZnO / CoO-CNT; and mixing the obtained ZnO / CoO-CNT with elemental sulfur, uniformly grinding, transferring into a reaction kettle, heating, preserving heat for a certain time, and cooling to room temperature, thereby obtaining the positive electrode material of the lithium-sulfur battery. The positive electrode material is prepared from the catalyst containing ZnO / CoO-CNT heterojunction and elemental sulfur through a melt diffusion method, so that the problems of poor conductivity of the elemental sulfur material, shuttle effect of polysulfide and slow sulfur conversion kinetics in the lithium-sulfur battery of an energy storage system can be effectively solved, and the coulombic efficiency and cycling stability of the lithium-sulfur battery are improved. The preparation method is simple in process, low in cost and low in energy consumption, and large-scale industrial production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur battery catalysis, and in particular relates to a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, a preparation method and an application thereof. Background Art

[0002] As energy consumption grows, humans are facing a huge environmental and resource crisis, and it is urgent to accelerate the development of renewable energy. Among them, lithium-ion batteries have changed people's lifestyles, promoted the widespread application and development of electronic devices such as portable cameras, mobile phones, and laptops, and achieved large-scale commercial applications. However, its mass / volume energy density has approached the theoretical limit and it is difficult to meet people's future demand for energy storage. The development of new secondary batteries with higher capacity and mass / volume energy density is the focus of the next step of research and development. Among the many energy storage systems that replace lithium-ion batteries, lithium-sulfur batteries have a high energy density (2600Wh kg –1 ), low cost, environmental friendliness and abundant sulfur resources have attracted more and more attention. However, lithium-sulfur batteries still have problems such as low utilization of active materials, shuttle effect of long-chain lithium polysulfides, and volume change of active materials during charging and discharging.

[0003] In response to these problems, researchers have modified the positive electrode materials, such as designing metal oxide catalysts, which can effectively inhibit the dissolution of polysulfides by adsorbing and converting polysulfides, thereby improving the electrochemical performance of the battery. The traditional method for preparing metal oxides is high-temperature calcination, but the long-term heat treatment (usually several hours) of the traditional preparation method leads to high energy consumption and manufacturing costs. The whole process takes a long time and has low production efficiency. For example, the nano high entropy oxide positive electrode material prepared by patent CN115594229A uses calcination conditions of 850-1000°C and insulation for 10-24h. The preparation cycle is long, the manufacturing cost is high, and it is difficult to achieve large-scale industrial production.

[0004] Therefore, developing a fast, efficient, cheap and environmentally friendly method for preparing lithium-sulfur battery positive electrode materials is crucial to the future development of new energy batteries. Summary of the invention

[0005] The present invention provides a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, a preparation method and an application thereof, so as to solve the problems existing in the prior art of long preparation cycle, high manufacturing cost and low production efficiency.

[0006] In order to achieve the above object, the present invention proposes the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, comprising the following steps:

[0008] Step 1: adding cobalt salt, zinc salt and urea into deionized water, performing hydrothermal synthesis, washing, centrifugal drying and obtaining zinc-cobalt layered double hydroxide;

[0009] Step 2: Mix zinc-cobalt layered double hydroxide and carbon nanotubes, grind them evenly, and press the obtained mixture into sheets for Joule heat treatment to obtain a ZnO / CoO-CNT heterojunction;

[0010] Step 3: After mixing the obtained ZnO / CoO-CNT heterojunction with elemental sulfur, grind and evenly transfer to a reactor, heat by melt diffusion method, keep warm for a certain period of time, and cool to room temperature to obtain a positive electrode material for a lithium-sulfur battery;

[0011] Furthermore, in the above step 1, the molar ratio of the cobalt salt to the zinc salt is 1:0.2-4.

[0012] Furthermore, in the above step three, the mass ratio of ZnO / CoO-CNT heterojunction catalyst to sulfur is 3:4-8.

[0013] Furthermore, in the above step 1, the hydrothermal synthesis temperature is 100-120° C., the insulation time is 8-12 h, and the drying temperature is 40-60° C., and the time is 10-12 h.

[0014] Furthermore, in the above step 2, the mass ratio of zinc-cobalt layered double hydroxide to carbon nanotubes is 1:0.2-4.

[0015] Furthermore, in the above step 1, the metal salt is a nitrate or a chloride.

[0016] Furthermore, in the Joule heat treatment of step 2, the output current is 30-60A, the output voltage is 30-60V, the number of pulses is 3-5 times, and the instantaneous temperature reaches 900-1200°C.

[0017] Furthermore, in the above step three, the temperature of the melt diffusion method is 150-160° C., and the insulation time is 8-12 hours.

[0018] The second aspect of the present invention provides a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst obtained by the above preparation method.

[0019] The third aspect of the present invention provides the use of the above-mentioned positive electrode material containing ZnO / CoO-CNT heterojunction catalyst in a lithium-sulfur battery, wherein the battery is assembled in sequence by at least a positive electrode sheet, an electrolyte, a separator, and a negative electrode metal lithium sheet, and the positive electrode sheet is made of a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] (1) The present invention first prepares a catalyst containing a ZnO / CoO-CNT heterojunction, wherein the catalyst uses carbon nanotubes as a carrier, and cobalt oxide and zinc oxide nanoparticles are loaded on the carbon nanotube carrier. The precursor is zinc-cobalt layered double hydroxide, which has a simple synthesis method and low cost. It is mixed with carbon nanotubes through ultrafast Joule heating technology. The ultrafast heating / cooling process and short reaction time promote the uniform dispersion of heterostructure catalyst nanoparticles, forming a large number of heterostructure interfaces, which can effectively prevent the catalytic activity from being attenuated due to aggregation.

[0022] (2) The present invention prepares a positive electrode material by melt diffusion method using a catalyst containing a ZnO / CoO-CNT heterojunction and elemental sulfur, wherein the electron transport channel formed by interconnected carbon nanotubes can promote the migration efficiency of electrons and enhance the conductivity of elemental sulfur. Zinc oxide and cobalt oxide provide abundant active sites for adsorbing polysulfides, limit the loss of active substances, further weaken the shuttle effect of polysulfides, and improve the electrochemical performance of sulfur electrodes. The prepared catalyst material is applied to the positive electrode of lithium-sulfur batteries, which can effectively solve the problems of poor conductivity of elemental sulfur materials, the shuttle effect of polysulfides, and slow sulfur conversion kinetics in lithium-sulfur batteries of energy storage systems, improve the coulombic efficiency and cycle stability of lithium-sulfur batteries, and improve the performance of lithium-sulfur batteries.

[0023] (3) The preparation method of the present invention has mild reaction conditions, simple process, low cost, and low energy consumption, and can efficiently and quickly prepare positive electrode materials containing ZnO / CoO-CNT heterojunction catalysts, thereby realizing large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The high-resolution TEM image and high-angle transmission scattering (HAADF-STEM) image and corresponding EDS elemental spectrum provided in Example 1 of the present invention;

[0025] Figure 2 The adsorption-desorption isotherm curve and pore size distribution diagram provided in Example 1 of the present invention;

[0026] Figure 3 The XRD diagram provided by Example 1 of the present invention;

[0027] Figure 4 The battery assembled from Examples 1, 2, and 3 of the present invention and Comparative Example 1 is 0.1 mV s -1 CV curves under scanning rate;

[0028] Figure 5 CV curves of the batteries assembled in Examples 1, 2, 3 of the present invention and Comparative Example 1 at different continuous scan rates;

[0029] Figure 6 The first cycle charge and discharge specific capacity diagram of the batteries assembled in Examples 1, 2, 3 of the present invention and Comparative Example 1 at a current density of 0.1C;

[0030] Figure 7 The cycle performance diagram of the battery assembled from Examples 1, 2, 3 of the present invention and Comparative Example 1 at a current density of 1C;

[0031] Figure 8 The performance comparison diagram of the batteries assembled in Examples 1, 2, 3 of the present invention and Comparative Example 1 at different rates;

[0032] Fig. 9 CV graphs of symmetrical batteries of Examples 1, 2, 3 of the present invention and Comparative Example 1, in which the electrolyte is 0.2M Li2S6 solution and a blank electrolyte. DETAILED DESCRIPTION

[0033] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific examples and drawings. The following examples are based on the technology of the present invention and provide detailed implementation methods and operating steps, but the protection scope of the present invention is not limited to the following examples.

[0034] The invention idea provided by the present invention is: firstly, zinc cobalt layered double hydroxide (ZnCo-LDH) is synthesized, zinc cobalt layered double hydroxide (ZnCo-LDH) is mixed with carbon nanotubes, and after grinding evenly, the obtained mixture is subjected to Joule heat treatment to obtain a derivative ZnO / CoO-CNT; after the obtained ZnO / CoO-CNT is mixed with elemental sulfur, the mixture is ground evenly and transferred to a reaction kettle, heated, kept warm for a certain period of time, and then cooled to room temperature to obtain a lithium sulfur battery positive electrode material.

[0035] Example 1: A method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, comprising the following steps:

[0036] Step 1: Weigh 1 mmol of Zn(NO)3·6H2O, 1 mmol of Co(NO)3·6H2O and 8 mmol of urea, add them into 60 ml of deionized water, stir them evenly with ultrasound, put them into a reactor, keep them at 120°C for 12 hours, wash the obtained precipitate with deionized water and ethanol by centrifugation three times, put them into a vacuum oven at 60°C and dry them for 12 hours to obtain ZnCo-LDH powder;

[0037] Step 2: Weigh 120 mg of CNT and 120 mg of ZnCo-LDH, grind and mix them evenly, press them into 15 mm discs using a tablet pressing mold and a tablet pressing machine, and perform Joule heat treatment: the output current is 60 A, the output voltage is 60 V, the pulse number is set to 5 times, and the instantaneous temperature reaches 1000 ° C to obtain a ZnO / CoO-CNT heterojunction catalyst;

[0038] Step 3: Grind and mix the ZnO / CoO-CNT heterojunction catalyst and sulfur element obtained in step 2 in a mass ratio of 3:7, seal them in a reactor, and perform melt diffusion treatment at 155° C. for 12 hours to obtain a lithium-sulfur battery positive electrode material.

[0039] Example 2: A method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, comprising the following steps:

[0040] Step 1: Weigh 1 mmol of Zn(NO)3·6H2O, 2 mmol of Co(NO)3·6H2O and 8 mmol of urea and add them into 60 ml of deionized water. The remaining preparation steps are the same as those in Example 1 to prepare the positive electrode material.

[0041] Example 3: A method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, comprising the following steps:

[0042] Step 1: Weigh 2 mmol of Zn(NO)3·6H2O, 2 mmol of Co(NO)3·6H2O and 8 mmol of urea and add them into 60 ml of deionized water. The remaining preparation steps are the same as those in Example 1 to prepare a positive electrode material for a lithium-sulfur battery.

[0043] Comparative Example 1: A method for preparing a positive electrode material, comprising the following steps:

[0044] Step 1: The preparation steps of ZnCo-LDH are the same as those in Example 1 above;

[0045] Step 2, physically grinding and mixing the prepared ZnCo-LDH and CNT to obtain ZnCo-LDH / CNT;

[0046] Step 3: Prepare the same as Example 1 to obtain Comparative Example 1.

[0047] Figure 1 The high-resolution TEM image and high-angle transmission scattering (HAADF-STEM) image and corresponding EDS elemental map of the ZnO / CoO-CNT heterojunction catalyst provided in Example 1 of the present invention. From the TEM, HAADF-STEM images and corresponding EDS elemental maps at different magnifications, it can be seen that the sample treated with Joule heat at high temperature successfully loaded a zinc oxide and cobalt oxide heterostructure on the CNT, and this heterostructure provides active sites that can chemically interact with LiPSs, thereby regulating and improving the anchoring, diffusion and conversion efficiency of LiPSs during the charge / discharge process of the lithium-sulfur battery.

[0048] Figure 2 The adsorption-desorption isotherm and pore size distribution diagram of the ZnO / CoO-CNT heterojunction catalyst provided in Example 1 of the present invention. The specific surface area of ​​the ZnO / CoO-CNT heterojunction catalyst calculated according to the BET equation is 146.8 m 2 g -1 , which helps to enhance its adsorption capacity for polysulfides.

[0049] Figure 3 This is the XRD diagram of the ZnO / CoO-CNT heterojunction catalyst provided in Example 1 of the present invention. Figure 2 It can be seen that the peaks appearing in the XRD pattern correspond to ZnO and CoO, which preliminarily proves that the ZnO / CoO-CNT heterojunction catalyst was successfully synthesized.

[0050] The positive electrode composite materials provided in Example 1 and Comparative Example 1 were respectively mixed with conductive carbon black and binder PVDF in a mass ratio of 8:1:1, and dispersant NMP was added, and the mixture was stirred to obtain a mixed slurry. The mixed slurry was coated on the surface of an aluminum foil with a coating thickness of 20 μm, and the mixture was vacuum dried at 60° C. for 12 h to obtain a lithium-sulfur battery positive electrode sheet containing a ZnO / CoO-CNT heterojunction catalyst.

[0051] Four types of lithium-sulfur batteries were assembled in sequence by assembling the positive electrode sheet, electrolyte, separator, and negative electrode metal lithium sheet. The test results are as follows:

[0052] Figure 4 The cells assembled from Examples 1, 2, 3 and Comparative Example 1 were tested at 0.1 mV S -1 CV curves at scanning rates. As can be seen from the figure, the peaks of the ZnO / CoO-CNT heterojunction catalysts prepared in Examples 1, 2, and 3 are sharper, the peak current is larger, and the spacing is smaller, indicating that they can quickly catalyze the conversion of polysulfides and have higher catalytic activity;

[0053] Figure 5The CV curves of the batteries assembled from Examples 1, 2, 3 and Comparative Example 1 at continuous scan rates. It can be seen from the figure that at different scan rates, the CV curves of Examples 1, 2, 3 still show more obvious redox peaks than the CV curve of Comparative Example 1, proving that they have faster reaction kinetics and lower internal resistance;

[0054] Figure 6 The first cycle charge and discharge specific capacity of the battery assembled in Examples 1, 2, 3 and Comparative Example 1 at a current density of 0.1C is shown in Figure 2. The initial discharge specific capacities of Example 1 and Comparative Example 1 are 1274.7 mAh g -1 , 1024.7mAh g -1 It can be seen that the material after Joule heat treatment will greatly improve the specific capacity of the lithium-sulfur battery during the charge and discharge cycle, making the battery show more excellent electrochemical performance;

[0055] Figure 7 The cycle performance diagram of the battery assembled in Examples 1, 2, 3 and Comparative Example 1 at 1C current density. The initial capacity of Example 1 is as high as 1123.4 mAh g -1 , the capacity decay rate remained at 53.48% after 300 cycles, indicating its excellent cycle stability;

[0056] Figure 8 The performance comparison diagram of the batteries assembled in Examples 1, 2, 3 and Comparative Example 1 at different rates. Example 1 can still provide 682.1 mAh g at 2C. -1 After being tested under different current density conditions, the discharge capacity of the battery is still 932.3mAh g when the current density returns to 0.1C. -1 The discharge specific capacity has good cycle reversibility and excellent rate performance;

[0057] Fig. 9 Symmetric cells composed of 0.2M Li2S6 solution and blank electrolyte for Examples 1, 2, 3 and Comparative Example 1 at 3 mV S -1 CV graph at scan rate. The redox peaks in the figure correspond to the transition between S8, Li2S6 and Li2S, indicating that it has better electrochemical catalytic activity.

[0058] The above is only a preferred embodiment of the present invention. The present invention can have other forms of embodiments according to the above preparation method, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst, characterized in that: The steps include: Step 1: adding cobalt salt, zinc salt and urea into deionized water, performing hydrothermal synthesis, washing, centrifugal drying and obtaining zinc-cobalt layered double hydroxide; Step 2: Mix zinc-cobalt layered double hydroxide and carbon nanotubes, grind them evenly, and then perform Joule heat treatment on the obtained mixture to obtain a ZnO / CoO-CNT heterojunction; Step 3: After mixing the obtained ZnO / CoO-CNT with elemental sulfur, grind them evenly and transfer them to a reactor, heat them using a melt diffusion method, keep them warm for a certain period of time, and then cool them to room temperature to obtain a lithium-sulfur battery positive electrode material.

2. The method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to claim 1, characterized in that: In the step 1, the molar ratio of the cobalt salt to the zinc salt is 1:0.2-4.

3. The method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to claim 2, characterized in that: In the step three, the mass ratio of the ZnO / CoO-CNT heterojunction catalyst to sulfur is 3:4-8.

4. The method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to claim 3, characterized in that: In the step 1, the hydrothermal synthesis temperature is 100-120°C, the insulation time is 8-12 h, and the drying temperature is 40-60°C, and the time is 10-12 h.

5. A method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to any one of claims 1 to 4, characterized in that: In the step 2, the mass ratio of zinc-cobalt layered double hydroxide to carbon nanotubes is 1:0.2-4.

6. The method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to claim 5, characterized in that: In the step 1, the metal salt is a nitrate or a chloride.

7. The method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to claim 6, characterized in that: In the Joule heat treatment of step 2, the output current is 30-60A, the output voltage is 30-60V, the number of pulses is 3-5 times, and the instantaneous temperature reaches 900-1200°C.

8. The method for preparing a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst according to claim 7, characterized in that: In the step 3, the temperature of the melt diffusion method is 150-160° C., and the insulation time is 8-12 hours. 9 . A positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst obtained by the preparation method according to claim 1 .

10. The use of a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst in a lithium-sulfur battery according to claim 1, characterized in that: The battery is prepared by assembling at least a positive electrode sheet, an electrolyte, a separator, and a negative electrode metal lithium sheet in sequence, and the positive electrode sheet is prepared from a positive electrode material containing a ZnO / CoO-CNT heterojunction catalyst.